The innovation ecosystem as a source of value creation : a value creation lever for open innovation - Julien, Odile de Saint (London : ISTE Ltd ; Hoboken, NJ : John Wiley & Sons, Inc., 2022)
Ecosystems have been present in the fields of economics and management for decades, and in recent years they have experienced rapid development. However, there is still no consensus on the definition of an innovation ecosystem. Using concrete examples, The Innovation Ecosystem as a Source of Value Creation proposes a unique model in order to refine the understanding, functions, advantages and disadvantages of innovation ecosystems. This model is based on both the iterative network and integrated value chain. The network supports the collaboration between actors and favors asset transfers articulated around the innovation process. This book highlights the transfer processes at work in the innovation ecosystem, as well as the roles of the actors in this integrated value chain. It presents how value creation is articulated around knowledge to generate value shared by all of the actors in the innovation ecosystem.
Front Matter -- Innovation Ecosystem: Definitions -- Innovation Ecosystem and Innovation Processes -- Modeling: Combination of Three Ecosystems -- The Actors of the Innovation Ecosystem -- Coherence and Interdependencies -- The Iterative Network: Collaboration and Typology -- Asset and Knowledge Transfers: The Integrated Value Chain -- Ecosystems and Strategies -- Ecosystems and Value Creation -- References -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 15, 2022).
John Wiley and Sons
Keywords: Technological innovations; Innovations; Technological innovations